Impact of COVID-19 pandemic and diabetes on mechanical reperfusion in patients with STEMI: insights from the ISACS STEMI COVID 19 Registry - De Luca, Giuseppe; Cercek, Miha; Jensen, Lisette Okkels; Marija Vavlukis; Calmac, Lucian; Johnson, Tom; Roura I Ferrer, Gerard; Ganyukov, Vladimir; Wojakowski, Wojtek; von Birgelen, Clemens; Versaci, Francesco; Ten Berg, Jurrien; et al. (Springer Science and Business Media LLC, 2020)
It has been suggested the COVID pandemic may have indirectly affected the treatment and outcome of STEMI patients, by avoidance or significant delays in contacting the emergency system. No data have been reported on the impact of diabetes on treatment and outcome of STEMI patients, that was therefore the aim of the current subanalysis conducted in patients included in the International Study on Acute Coronary Syndromes-ST Elevation Myocardial Infarction (ISACS-STEMI) COVID-19.
Keywords: STEMI; myocardial infarction; COVID-19